'Guardare' il paesaggio Breve vademecum per gli Osservatori del Paesaggio in Toscana - Massimo Morisi (Territori, 2016)
This volume was born from a recognition of the experiences and warnings which were needed for the creation of a landscape observatory in Tuscany, and for the definition of the network and interactive methods which the observatory itself can use while aiming at its own operational effectiveness. The analysis was carried out during the formation stage of the Landscape Plan of Tuscany and during the collaboration which the Regional Authority has promoted with the Inter-University Centre of Territory Sciences. Starting from the examination of the organizational and functional models characterizing the main European and Italian experiences, in the plurality of regulatory contexts, forms of landscape planning and regulation and practices of cultural and association mobilization of the reference populations, some working hypotheses are formulated and calibrated on the Tuscan situation.